Mutational Landscape of Intermediate-Risk and Poor-Risk Acute Myeloid Leukemia (AML) Adult Patients by Next-Generation Sequencing (NGS): One Academic Center's Experience. (21st September 2018) - Chung, Betty; Thomas, Jessica; Olsen, Randall
Abstract: In acute myeloid leukemia (AML), specific cytogenetic abnormalities and gene mutations possess prognostic significance and are used in the risk stratification of these patients for treatment. To characterize the mutational landscape of our acute myeloid leukemia patients, we reviewed the results of next-generation sequencing (NGS) for 54 myeloid neoplasm (MN)–related genes from 58 specimens (53 bone marrow, 5 whole blood) from 44 patients (21 men, 23 women, median age: 63 years, range: 21–89 years) with suspicion or history of a myeloid neoplasm obtained from May 2016 through December 2017 at our institution. These samples (31 diagnostic, 22 staging, 5 surveillance) were categorized as de novo AML (20.7%, n = 12), AML with MDS-related changes or secondary to MDS (AML-MRC: 15.5%, n = 9; sAML: 5.2%, n = 3), negative for suspected MN (15.5%, n = 9), myeloproliferative neoplasm (MPN: 12.1%, n = 7), relapsed/refractory AML (r/r AML: 12.1%, n = 7), therapy-related AML (t-AML: 6.9%, n = 4), myelodysplastic syndrome (MDS: 6.9%, n = 4), MDS/MPN (3.4%, n = 2), and AML in complete remission (1.7%, n = 1). Specifically, 36 specimens (32 bone marrow, 4 whole blood) from 22 patients (15 men, 7 women, median age: 61.5 years, range: 27–89 years) were found to have a diagnosis of AML during some point in treatment at our institution and 21 of 22 patients were not in remission at the time of NGS testing. Of these 22 patients, 6 were eventually lost to follow-up (4 palliative care/hospice), 5 were posttransplant (2 MMUD, 2 MUD, 1 MRD), and 3 are now deceased. Of the 22 AML patients, 23.8% and 9.5% were classified as intermediate risk with and without abnormal karyotype, respectively, 61.9% as poor risk, and 4.8% as unclassifiable by NCCN guidelines at diagnosis. Of AML samples, 67.6% were positive for somatic variants with an average of 2.7 reported variants and 1.3 variants of undetermined significance per patient. The most commonly mutated gene in our AML patients was DNMT3A followed by TP53 and FLT3 -ITD (often with DNMT3A comutation), which were also the three most mutated genes in our poor-risk patients. Interestingly, the two intermediate-risk with normal karyotype patients both shared a SFSR2 missense mutation at the Pro95 residue, and the patient with the higher marrow blast burden had additional mutations in ASXL1 and RUNX1 . Potentially actionable mutations in our patients were identified in the FLT3, IDH1/IDH2, JAK2 (Val617Phe), KIT, and DNMT3A genes and the most commonly acted upon for targeted treatment were FLT3 -ITD mutations with Midostaurin.